Voice climate, gender equality and well-being in the South African banking sector - Praise Choeni; Sebastiaan Rothmann; Mirna Nel (SA Journal of Industrial Psychology)
Orientation: This study addressed the persistent challenge of gender inequality in the banking sector in South Africa, where women face disparities in pay, career progression and leadership representation. Using the capability approach highlights the importance of fostering a supportive voice climate that encourages employees, especially women, to express concerns and contribute meaningfully to workplace dynamics.